WT-1, BAALC, and ERG Expressions in Iranian Patients with Acute Myeloid Leukemia Pre- and Post-chemotherapy - Hossein Mehralizadeh; Mohammad Reza Aliparasti; Mehdi Talebi; Shabnam Salekzamani; Shohreh Almasi; Morteza Raeisi; Mehdi Yousefi; AliAkbar Movassaghpour (Tabriz University of Medical Sciences, 2021)
Purpose: Acute myeloid leukemia (AML) is the most prevalent acute leukemia in adults. It possesses different cytogenetic and molecular features. The expression of Wilms tumor-1 (WT1), brain and acute leukemia, cytoplasmic (BAALC) and ETS-related gene (ERG) might be considered as prognostic factors in AML patients. The aim of this study was to determine the mRNA expressions of WT-1, BAALC and ERG genes in bone marrow of mononuclear cells and their effects on complete remission in the Iranian AML patients, pre- and post- chemotherapy. Methods: Forty AML patients with normal karyotype were evaluated. The mRNA gene expressions were measured with quantitative real-time PCR in bone marrow of mononuclear cells of AML patients at the baseline and after chemotherapy. The subtypes of AML and flow cytometry panel were also assessed. Complete remission (CR) after the treatment was addressed for all patients. Results: The mRNA expressions of WT-1, BAALC and ERG were significantly decreased after the treatment (p= 0.001, 0.017, 0.036). WT-1 mRNA expression was inversely correlated with CR after chemotherapy (P =0.024). There was also significant correlation between baseline expression of BAALC and CR (P=0.046). No significant correlation was observed between ERG and CR pre- and post- chemotherapy (P =0.464 and 0.781). There was also significant correlation between BAALC mRNA expression and CD34+ (P <0.001). Conclusion: The present study showed that WT-1 decreased significantly after standard chemotherapy which could have favorable effects on CR. Also, the high expression of BAALC could have a poor prognostic role in AML patients. The identification of these gene expressions can be an efficient approach in targeted therapy among AML patients.